ECOSYSTEM-BASED CRM INTEGRATION IN MULTI-UNIT UMRAH ENTERPRISES: A CASE STUDY OF TIGA MAHAREWA GROUP - Harmina, Harmina; Basir, Mustika Kusuma; Burhanuddin, Fia Fauzia; Triany, Novika Ayu; Pagiling, Novieyanty (International Journal of Economics, Business and Accounting Research (IJEBAR), 2025)
This research explores the strategic imperative of Customer Relationship Management (CRM) integration within the Tiga Maharewa Group’s multi-unit business ecosystem, focusing on Umrah services. Qualitative inquiry and strategic analysis (IFAS/EFAS) revealed severe operational fragmentation (silos) and a critical lack of unified data, empirically positioning the firm in a strategic turnaround condition. To resolve this strategy-structure misalignment, the study developed a Conceptual Strategic Integration Model by synthesizing TOWS analysis and a revised Business Model Canvas. The proposed model is founded on Shared CRM Membership  and Collaborative Promotion, and crucially expands customer segmentation to formally incorporate Agents and External Merchants to facilitate Value Co-Creation. The study’s core contribution is a four-stage conceptual roadmap that recommends pragmatic implementation steps, from securing an executive mandate to system standardization. This model and roadmap provide a necessary strategic framework for the Tiga Maharewa Group to transform its siloed operations into a cohesive, data-driven ecosystem, ensuring enhanced efficiency, long-term competitive advantage, and alignment with the Islamic principle of Ta'awun (cooperation).